Study protocol—investigation of the Delirium Observation Screening Scale (DOSS) for the routine detection of delirium in the care home setting: a prospective cohort study - Teale, Elizabeth (BMJ Open, 2016)
INTRODUCTION: Delirium is a common and distressing condition associated with frailty, dementia and comorbidity. These are common in long-term care settings. Residents in care homes are therefore at particular risk of delirium. Despite this, methods to detect delirium in care homes are lacking, with existing diagnostic tools taking too long, or requiring specific training to deliver. This limits their feasibility for use for the routine detection of delirium by care home staff. Routine screening for delirium in care homes would allow timely attention to exacerbating factors to attenuate the episode, and facilitate future research into delirium in the care home environment. METHODS: Residents from 4 large care homes will be asked to consent (or their consultees asked to provide a declaration of agreement) to participate in the study. Care home staff will administer the 25-item Delirium Observation Screening Scale (DOSS)—a delirium screening tool based on observed behaviours—and this will be tested against the research standard Confusion Assessment Method (CAM) administered by trained research assistants performed two times per week for all participating residents. ANALYSIS: Sensitivity, specificity, positive and negative predictive values, likelihood ratios and a diagnostic OR will be calculated for the detection of delirium with the 25-item DOSS. The feasibility of routine delirium screening and the scaling properties of the 25-item DOSS will also be explored. ETHICS AND DISSEMINATION: For residents lacking capacity to participate, a consultee will be approached for a declaration of agreement for inclusion in the study. Results will be published in peer-reviewed journals and disseminated in written format to clinical commissioning groups, general practitioners and relevant third parties. TRIAL REGISTRATION NUMBER: ISRCTN14608554.